2015
DOI: 10.5861/ijrsp.2015.1103
|View full text |Cite
|
Sign up to set email alerts
|

Are daily spiritual experiences, self-esteem, and family harmony predictors of cyberbullying among high school student?

Abstract: Currently, the incidence of cyberbullying increase widespread among children and adolescents in Indonesia. One of eight parents stated that their children have been victims of abused and humiliation through online media. As many as 55% of parents said they knew one child experienced cyberbullying. This study aims to investigate cyberbullying related to daily spiritual experiences, self-esteem and family harmony. Present study also explores the factors that lead to the emergence of the cyberbullying phenomenon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
6
0
7
Order By: Relevance
“…P e r u n d u n g a n d i k a l a n g a n s i s w a di sekolah pernah dilakukan oleh Rahayu (2012); Maya (2015), dan Budiarti (2016). Perundungan siber terhadap anak dan orang dewasa pernah dikaji oleh Safaria (2015). Sementara beberapa contoh kasus perundungan siber di dunia pernah diteliti oleh (Haryati, 2014).…”
Section: Pendahuluanunclassified
“…P e r u n d u n g a n d i k a l a n g a n s i s w a di sekolah pernah dilakukan oleh Rahayu (2012); Maya (2015), dan Budiarti (2016). Perundungan siber terhadap anak dan orang dewasa pernah dikaji oleh Safaria (2015). Sementara beberapa contoh kasus perundungan siber di dunia pernah diteliti oleh (Haryati, 2014).…”
Section: Pendahuluanunclassified
“…The internet has become a necessity among adolescents (Nixon, 2014;Quarshie, 2009). The existence of the internet has positive impacts including the ease of accessing information, the opportunity to interact with people who live far apart, the availability of various entertainment media, and the convenience of online shopping (Rahayu, 2012;Redekopp & Kalanda, 2014;Safaria, 2015). On the other hand, the internet also has negative impacts including the dissemination of irresponsible news, cybercrimes, and internet addiction leading to various issues including cyberbullying, just to name a few (Lazuras, Barkoukis, Ourda, & Tsorbatzoud, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A similar finding has been found in Indonesia. For example, Safaria (2015) found that 9% of students claimed to have engaged in cyberbullying several times, and 40% of students claimed to have been victims of bullying. In the subsequent study, it was found that 80% of junior high school students and 83% of high school students claimed to have been victims of cyberbullying (Safaria, 2016;Safaria, Tentama, & Suyono, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Kemudian bentuk perundungan siber di media sosial dan pencegahannya dilakukan oleh Rastati (2016). Perundungan siber terhadap anak dan orang dewasa pernah dikaji oleh Safaria (2015). Selain itu, penelitian perundungan yang terjadi di tempat kerja dilakukan oleh Silviandari (2018).…”
Section: Pendahuluanunclassified